الاعتراضات على تراجم صحيح البخاري وأجوبة الحافظ ابن حجر عنها في كتابه "فتح الباري": دراسة تحليلية مقارنة من أول كتاب بدء الوحي إلى آخر كتاب الإيمان: Answers from al-Hafiz Ibn Hajar in His Book “Fath Al-Bari” on Objections on Tarajim (Sub-Sections) and No Introduction in Sahih Al-Bukhari: A Comparative Analytical Study from Chapter of ‘the Beginning of the Revelation’ until the End of the Chapter of ‘Faith’ (Maʿālim al-Qurʾān wa al-Sunnah, 2021)
This research aims to compile the points of contention mentioned by Al-Hāfiz Ibn Hajar in Fath Al-Barī concerning the Tarājim (Sub-Sections) of Sahīh Al-Bukharī and his respective answers to them. The research analysis of this study begins with the chapter titled ‘The Beginning of the Revelation’ until the end of the chapter entitled ‘Faith’. The answers presented by Ibn Hajar are analysed and compared to the answers of other scholars who authored commentaries on Sahīh Al-Bukharī from those scholars who preceded him or were his contemporaries. The problem addressed in this research lies in the fact that many scholars while acknowledging the authenticity of Sahīh Al-Bukharī, its high status, the excellence and superiority of its author, did not agree with al-Bukhari in all the subsidiary issues mentioned therein. In fact, some scholars disputed or objected al-Bukhari in certain issues, stating that al Bukharī erred or assumed something wrongly. At the same time, other scholars defended al Bukharī on these issues. Hence, this research aims to study these objections and analyse them to clarify what these objections are and explain the scholars' approach in responding to them. The importance of the research is that it exemplifies an aspect of the methodology used by hadith scholars in criticising the Tarājim of books and discusses the criticisms made by these scholars and the counter responses provided. Methods employed by the researcher in this study include the inductive approach to collect the objections, the descriptive-analytical method to explain the objections and clarify the answers given by Ibn Hajar on the objections, and lastly, the comparative approach to compare the answers provided by Ibn Hajar versus other scholars. The most important results of the research are summarised in the number of objections to the Tarājim of Sahīh Al-Bukharī, which Ibn Hajar mentioned in Fath Al-Barī from the chapter titled ‘The Beginning of the Revelation’ up to the end of the chapter entitled ‘Faith’, amounting to eight (8) objections distributed amongst eight (8) Tarājim out of a total of forty-one (41) Tarjimah used in this study. These objections are divided into four categories which are: disregarding textual evidence (one objection); the negation of the existence of congruence between the Tarjamah and textual evidence (five objections); repetition of a Tarjamah (one objection); and Tarjamah strengthening an incorrect view (one objection). Ibn Hajar used a varied approach in responding to these objections, namely by combining the application of the Qur’an and the Sunnah, reason, fundamentals of jurisprudence and hadith, as well as citing statements of previous commentators.